Business for higher awards - Needham, David; Dransfield, Robert; Coles, Martin; Harris, Rod.; Rawlinson, Maureen ([S.l.] : Heinemann Educational Publishers, 1999)
This student text offers full coverage of the core units for Business HNC/D, reinforcing the theory with case studies and activities to develop students' knowledge and understanding.
Keywords: business.marketing,management